A Rare Case of Granulomatous Interstitial Nephritis in a Patient With COVID-19. (July 2022) - Alotaibi, Manal; Ellis, Carla; Wadhwani, Shikha; Peleg, Yonatan
Acute kidney injury (AKI) in patients with coronavirus disease 2019 (COVID-19) is common, especially among severely ill patients. While acute tubular necrosis (ATN) is one of the most common findings in published kidney biopsy series for patients with COVID-19 infections, a number of glomerular pathologies have been described as well. Among glomerular pathologies in COVID-19, COVID-19-Associated Collapsing Glomerulopathy (COVAN) remains the most common pattern of injury. Patients with 2 high-risk APOL1 alleles appear to be at increased risk for COVAN, similar to other forms of collapsing glomerulopathy such as HIV-Associated Nephropathy. Acute interstitial nephritis (AIN) is a less common finding in patients with COVID-19 and reported cases have been mild. Reports of a subtype of AIN, granulomatous interstitial nephritis (GIN), among COVID-19 patients are extremely rare and have not been reported in association with COVAN. Here, we report a case of COVAN associated with severe GIN.